Sustainable Residential Landscapes:An International Perspective - Smith, Carl (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a compilation of 10 recently published academic articles addressing sustainable residential landscape design and planning across geographies, scales, and perspectives: from American rain garden design to South Korean urban forestry; from Mexican community open space design to Australian neighborhood park planning; and from Chinese urban design to Bolivian land-use change. This volume brings together authors from a growing community of landscape sustainability scholars of landscape architecture and architecture; planning and construction; ecology and horticulture; agricultural and environmental sciences; and health, exercise, and nutrition. In summary, these papers address facets of a fundamental challenge for the 21st century: the design and planning of sustainable and resilient human settlements.